Effects of Protective Mechanical Ventilation With Different PEEP Levels on Alveolar Damage and Inflammation in a Model of Open Abdominal Surgery: A Randomized Study in Obese Versus Non-obese Rats - Maia, Lígia de A.; Fernandes, Marcos V. S.; Santos, Raquel S.; Agra, Laís C.; Carvalho, Anna Carolinna; Rocha, Nazareth de N.; Oliveira, Milena V.; Santos, Cíntia L.; Morales, Marcelo M.; Capelozzi, Vera L.; Souza, Sergio A. L.; Gutfilen, Bianca; et al. (Frontiers in Physiology, 2019)
Intraoperative positive end-expiratory pressure (PEEP) has been proposed to restore lung volumes and improve respiratory function in obesity. However, the biological impact of different PEEP levels on the lungs in obesity remains unknown. We aimed to compare the effects of PEEP = 2 cmH2O versus PEEP = 6 cmH2O during ventilation with low tidal volumes on lung function, histology, and biological markers in obese and non-obese rats undergoing open abdominal surgery. Forty-two Wistar rats (21 obese, 21 non-obese) were anesthetized and tracheotomized, and laparotomy was performed with standardized bowel manipulation. Rats were randomly ventilated with protective tidal volume (7 ml/kg) at PEEP = 2 cmH2O or PEEP = 6 cmH2O for 4 h, after which they were euthanized. Lung mechanics and histology, alveolar epithelial cell integrity, and biological markers associated with pulmonary inflammation, alveolar stretch, extracellular matrix, and epithelial and endothelial cell damage were analyzed. In obese rats, PEEP = 6 cmH2O compared with PEEP = 2 cmH2O was associated with less alveolar collapse (p = 0.02). E-cadherin expression was not different between the two PEEP groups. Gene expressions of interleukin (IL)-6 (p = 0.01) and type III procollagen (p = 0.004), as well as protein levels of tumor necrosis factor-alpha (p = 0.016), were lower at PEEP = 6 cmH2O than at PEEP = 2 cmH2O. In non-obese animals, PEEP = 6 cmH2O compared with PEEP = 2 cmH2O led to increased hyperinflation, reduced e-cadherin (p = 0.04), and increased gene expression of IL-6 (p = 0.004) and protein levels of tumor necrosis factor-alpha (p-0.029), but no changes in fibrogenesis. In conclusion, PEEP = 6 cmH2O reduced lung damage and inflammation in an experimental model of mechanical ventilation for open abdominal surgery, but only in obese animals.